A cascade of care for diabetes in people living with HIV in a tertiary care center in Mexico City - Cristian E. Espejo-Ortiz; Nancy Sierra-Barajas; Angelina Silva-Casarrubias; Lorena Guerrero-Torres; Yanink Caro-Vega; Yamile G. Serrano-Pinto; Alvaro Lopez-Iñiguez; Juan G. Sierra-Madero; Brenda E. Crabtree-Ramírez (HIV Research & Clinical Practice)
Background Diabetes affects 4.5% of people living with HIV in Mexico. This study aims to describe the diabetes cascade of care (DMC) in people with HIV in a tertiary center in Mexico City. Methods We conducted a single-center review of people with HIV aged over 18, using medical records of active people enrolled at the Instituto Nacional de Ciencias Médicas y Nutrición Salvador Zubirán (INCMNSZ) HIV Clinic (HIVC). Our analysis focused on their last visit to describe the DMC, aiming to identify gaps in control goals. We included people who had a consultation within the 12 months preceding May 2020. Results Out of the 2072 active people, medical records were available for 2050 (98.9%). Among these, 326 people (15.9%) had fasting glucose (FG) abnormalities, of which 133 (40.7%) had diabetes. The prevalence of diabetes among people with HIV was of 6.4% (133/2050). Regarding the DMC, the following proportions of people achieved control goals: 133/133 (100%) received medical care in the last 12 months, 123/123 (100%) had blood pressure (BP) <140/90 mmHg, 73/132 (55.3%) had LDL cholesterol (c-LDL) <100 mg/dl, 63/132 (47.7%) had FG <130 mg/dl, 50/116 (43.1%) had glycosylated hemoglobin (HbA1c) <7%. ABC goals (HbA1c <7%, c-LDL <100 mg/dl, BP <140/90 mmHg) were met in 28/109 (25.6%) people. 126/133 (94%) people with HIV achieved HIV-viral load <50 copies/mL. Conclusions Despite the high rate of viral suppression among people with HIV and diabetes, significant challenges remain in achieving comprehensive diabetes control. These findings highlight the need for targeted interventions to improve metabolic outcomes and the overall management of diabetes in people with HIV.